2021
DOI: 10.3389/fphar.2021.674807
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Intestinal Microbiota in Colorectal Cancer

Abstract: Colorectal cancer is a multifactorial disease involving genetic, environmental, and lifestyle risk factors. Intestinal microbiota plays an important role in the occurrence and development of colorectal cancer. Studies have shown that the behavior of intestinal microbiota can lead to pathological changes in the host intestine, which can be divided into epigenetic changes and carcinogenic changes at the gene level, and ultimately promote the formation and development of colorectal cancer. Intestinal microbiota i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 69 publications
0
19
0
Order By: Relevance
“…Numerous studies have shown that intestinal microbes are closely related to the development of intestinal diseases, and some of them have been found to be involved in the deterioration of colorectal cancer (CRC), such as Fusobacteriumnuleatum , Escherichia coli , Bacteroides fragilis , campylobacter jejuni , etc. [ 3 ]. Other bacteria can delay the development of CRC by regulating immune response, improving intestinal barrier function and inhibiting cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that intestinal microbes are closely related to the development of intestinal diseases, and some of them have been found to be involved in the deterioration of colorectal cancer (CRC), such as Fusobacteriumnuleatum , Escherichia coli , Bacteroides fragilis , campylobacter jejuni , etc. [ 3 ]. Other bacteria can delay the development of CRC by regulating immune response, improving intestinal barrier function and inhibiting cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…There is great potential for tumorigenetic pathway modulation by probiotics, such as L. acidophilus and L. plantarum [8]. Synbiotics are reportedly more efficient than probiotics in reducing epithelial proliferation and the increased efficacy of interventions seems to be linked to host microbial profile, which is less altered in early carcinogenesis [58].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the proinflammatory state associates with a reduction of beneficial bacteria from genera such as Ruminococcus, Bifidobacterium, Lactobacillus, and Clostridiales [7]. Several studies reported several main species constituting the bacterial signature of CRC patients including Fusobacterium nucleatum, Escherichia coli, Bacteroides fragilis, and Entreococcus faecalis [8,9]. Other certain strains are also associated with specific points in the progression towards CRC, for example, Oscillospira (Ruminococcaceae), is depleted in the transition from adenoma to stage 0 CRC, whereas Haemophilus is depleted later, towards early-stage CRC [4].…”
Section: Introductionmentioning
confidence: 99%
“…Although, interestingly in adults infected with CAP species E. faecium was reported as decreased abundance compared to healthy controls [30]. Not all Enterococcus species are pathobionts, but Enterococcal blooms have been reported in gastric and colorectal cancers [68]. Enterococci are clinically important as many strains have a high level of natural antibiotic resistance [29].…”
Section: Plos Onementioning
confidence: 99%